Promoting Youth Entrepreneurship and Employability through Non-Formal and Informal Learning: The Latvia Case - Pigozne, Tamara (CEPS journal, 2019)
This paper presents some results of the research on ‘Adult education resources to reduce youth unemployment’, which is a part of the project ‘Implementation of the European agenda for adult learning’. The research applies a mixed-method approach (quantitative and qualitative data analysis). The purpose of the paper is to identify the most/least-efficient non-formal and informal learning methods, forms, and initiatives to promote youth entrepreneurship and employability in Latvia as well as to show the relationship between the profile of young adults and their opinion on these methods, forms, and initiatives. The findings show that the young adults stressed the importance of cooperation with employers in organising educational activities, field trips as well as the necessity of having internships, projects, and meetings with entrepreneurs to learn from their experience. The most efficient non-formal and informal learning methods, forms, and initiatives to promote youth entrepreneurship and employability in Latvia are as follows: internship in a company or institution, projects, other persons’ experience and success stories, and training enterprises. The least efficient ones are mentoring, business incubators, coaching, individual work/action plan for the young people, business clubs, and business start-up funds/grants. The opinion of young adults on all aspects of non-formal and informal learning methods, forms, and initiatives depends on their profile (gender, education level, employment status, learning experience, etc.).